Adaptive Control of the Meiotic Recombination Landscape by DNA Site-dependent Hotspots With Implications for Evolution - Protacio, Reine U.; Davidson, Mari K.; Wahls, Wayne P. (Frontiers in Genetics, 2022)
Meiosis is an essential component of the sexual life cycle in eukaryotes. The independent assortment of chromosomes in meiosis increases genetic diversity at the level of whole chromosomes and meiotic recombination increases genetic diversity within chromosomes. The resulting variability fuels evolution. Interestingly, global mapping of recombination in diverse taxa revealed dramatic changes in its frequency distribution between closely related species, subspecies, and even isolated populations of the same species. New insight into mechanisms for these evolutionarily rapid changes has come from analyses of environmentally induced plasticity of recombination in fission yeast. Many different DNA sites, and where identified their binding/activator proteins, control the positioning of recombination at hotspots. Each different class of hotspots functions as an independently controlled rheostat that modulates rates of recombination over a broad dynamic range in response to changing conditions. Together, this independent modulation can rapidly and dramatically alter the global frequency distribution of recombination. This process likely contributes substantially to (i.e., can largely explain) evolutionarily rapid, Prdm9-independent changes in the recombination landscape. Moreover, the precise control mechanisms allow cells to dynamically favor or disfavor newly arising combinations of linked alleles in response to changing extracellular and intracellular conditions, which has striking implications for the impacts of meiotic recombination on evolution.